A Prospective Study of Non‐Surgical Primary Rhinoplasty Using a Polymethylmethacrylate Injectable Implant. Issue 3 (18th January 2014) - Rivkin, Alexander
<x xml:space="preserve">Abstract</x> Background Nonsurgical rhinoplasty involves the use of injectable fillers to improve the contours of the nose. It has become a widely practiced procedure since this author first popularized it in 2003. The use of permanent fillers in nonsurgical rhinoplasty has not been well documented, especially in this country. Objectives To demonstrate the safety and effectiveness of a polymethylmethacrylate (PMMA)‐based filler for nonsurgical rhinoplasty. Methods and Materials Eligible subjects underwent up to three injection sessions with a commercially available PMMA product and were followed for 1 year. Efficacy was assessed according to evaluator grading of subjects and digital image analysis of standardized photographs. Results Nineteen subjects were enrolled and followed to conclusion. Average improvement in global score was more than one point observed on day 90 and lasting through 1 year. Eight of 10 subjects showed improvement according to digital image analysis at 1 year. Subject satisfaction was high throughout the study. Adverse events were minimal and well tolerated. Conclusion Filler rhinoplasty using a PMMA‐based injectable filler is safe and effective. This is the first study documenting the use of PMMA for this indication. Longer‐term follow‐up is needed to demonstrate persistence of improvement.